The Phenomenon of Juvenile Delinquency that Occurs in the Era of Globalization - Agus Sarwanto (Eastasouth Institute, 2023)
Youth is the future asset of a nation. But nowadays, a lot is happening to teenagers, such as drugs and motorcycle gangs. This is a familiar problem. Juvenile delinquency includes all behavior that deviates from criminal law norms committed by juveniles. This study aims to determine the causes, impacts, and solutions to juvenile delinquency. The research method used is a literature review or literature review with qualitative data analysis. The variable in this study is juvenile delinquency in the era of globalization. From the results of this study, many internal and external factors cause juvenile delinquency that needs attention. In addition, juvenile delinquency can impact oneself, family, and society.